COVID 19 RISK ASSESSMENT AS A STRENGTHENING OF EARLY AWARENESS AND RESPONSE SYSTEMS WITH THE PERSONAL INARISK APPLICATION - Abdul Hakim Zakkiy Fasya; Priyo Mukti Pribadi Winoto; Dwi Handayani; Mursyidul Ibad; Nur Masruroh; Dayu Satriya Wibawa (Journal of Health Community Service, 2021)
The limited management of the surveillance system in Trenggalek caused the absence of an early warning alert and response system (EWARS) if the infectious disease situation leads to outbreaks. The current condition in the community, that there were still many confusing issues related to Covid19, which caused paranoia to occur. It will be difficult to do early detection and immediate treatment as a form of prevention of severity. Using the InaRISK Personal application, participants were invited to conduct an independent assessment of Covid19 transmission risks. Providing materials, mentoring, and evaluating, did this method. The results knew that participants feel the use of the application in awareness and preventing the transmission of Covid19. However, there were still complaints about application operations, such as disturbances, errors, and difficulty in determining the location point. Therefore, it is necessary to improve the functions and features of the application, which are used easily and comfortably.